Identification of core components of the exon junction complex in trypanosomes - Bercovich, Natalia (2009)
In animal cells, the exon junction complex (EJC) is deposited onto mRNAs during the second step of splicing, 20-24 nt upstream of the exon-exon junction. The EJC core contains four proteins: Mago, Y14, eIF4AIII and Btz. In trypanosomes, cis-splicing is very rare but all mRNAs are subject to 5′ trans-splicing of a 39-nt RNA sequence. Here we show that trypanosomes have a conserved Mago and a divergent Y14 protein, but we were unable to identify a Btz orthologue. We demonstrate that Mago and Y14 form a stable heterodimer using yeast two hybrid analyses. We also show that this complex co-purifies in vivo in trypanosomes with a protein containing an NTF2 domain, typically involved in mRNA transport.